Cross border transactions and tax treaties theory and practice - Khan, Ahmad (Singapore : Petrosin Info Tech ; Rawalpindi : [Stockist] Interface Technologies, 2000)
Includes bibliographical references (p. [468]-473) and index.
Keywords: Double taxation; International business enterprises -- Taxation -- Law and legislation; Income tax -- Foreign income